Exploring Transnational Dimensions of Activism in Contemporary Book Culture: Ons Klyntji and Afrikaner Activism - Klingenberg, Jana; Miller, Samantha (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
Afrikaans developed in South Africa out of an interaction among a variety of peoples. In the beginning, Afrikaans was considered a language spoken by the lower classes, but it rose from this low position to become an official language in 1925. After the National Party started to govern South Africa in 1948, Afrikaans became the language of the oppressor during apartheid. Post‑apartheid, Afrikaners questioned their identity, feeling conflicted between pride and shame.The magazine Ons Klyntji was established in 1896 to foster a literary culture and shape Afrikaner identity, and still exists today. Throughout its publication history, the magazine was used to promote progressive causes: first in the creation of an Afrikaans literature, and then as a vehicle for protest by Afrikaners against apartheid. Both these causes developed out of a need to find a distinct identity amongst Afrikaners. The researchers argue that the publishing of Ons Klyntji has contributed positively to progressive political and social change with regards to Afrikaner identity, particularly in the post‑apartheid period.